ELABORATION OF HIGH-VOLTAGE PULSE INSTALLATIONS AND PROVIDING THEIR OPERATION PROTECTIVE MEASURES - А. М. Hashimov; E. J. Gurbanov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article presents design engineering methods for the high-voltage pulse installations of technological purpose for disinfection of drinking water, sewage, and edible liquids by high field micro- and nanosecond pulsing exposure. Designing potentialities are considered of the principal elements of the high-voltage part and the discharge circuit of the installations towards assuring the best efficient on-load utilization of the source energy and safe operation of the high-voltage equipment. The study shows that for disinfection of drinking water and sewage it is expedient to apply microsecond pulse actions causing the electrohydraulic effect in aqueous media with associated complex of physical processes (ultraviolet emission, generation of ozone and atomic oxygen, mechanical compression waves, etc.) having detrimental effect on life activity of the microorganisms. In case of disinfecting edible liquids it is recommended to use the nanosecond pulses capable of straight permeating the biological cell nucleus, inactivating it. Meanwhile, the nutritive and biological values of the foodstuffs are saved and their organoleptic properties are improved. It is noted that in elaboration process of high-frequency pulse installations special consideration should be given to issues of the operating personnel safety discipline and securing conditions for the entire installation uninterrupted performance. With this objective in view the necessary requirements should be fulfilled on shielding the high- and low-voltage installation parts against high-frequency electromagnetic emissions registered by special differential sensors. Simultaneously, the abatement measures should be applied on the high-voltage equipment operational noise level. The authors offer a technique for noise abatement to admissible levels (lower than 80 dB A) by means of coating the inside surface with shielded enclosure of densely-packed abutting sheets of porous electro-acoustic insulating material.